PENGARUH PEMANFAATAN SISTEM INFORMASI AKADEMIK (SISKA) TERHADAP KINERJA INDIVIDUAL DENGAN KEGUNAAN PERSEPSIAN SEBAGAI VARIABEL MODERATING - Aulia, Dwi Himma; Widijoko, Grace (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The objective of research is to understand the influence of the use of academic information system (SISKA = sistem informasi akademik) on individual performance with the perceived useful as the moderating variable. Research population includes employees of Faculty of Economic and Business, University of Brawijaya Malang, which the total is 112 respondents. Sampling method is purposive sampling. All population members meet sample criteria, but the sample is only those meeting research criteria. The employee who has used SISKA is 45 freelances and 67 civil servants. The sample which meets criteria is counted to 71 respondents. Data are collected through questionnaire. The questionnaire has been examined with reliability and validity tests. The classical assumption test includes multi-collinearity test, normality test and heteroscedasticity test. Hypothesis test is followed by T-test. Result of research indicates that the variable of the use of academic information system (SISKA) has positive and significant impact on individual performance. the variable of perceived useful is moderating the variable of the use of academic information system (SISKA) which is then influencing individual performance, and in such that, the variable of perceived useful represents the moderating variable. Keywords: The Use of Information System, Perceived Useful, Individual Performance